Subarachnoid Hemorrhage with Negative Initial Digital Subtraction Angiography: Subsequent Detection of Aneurysms and Complication Rates of Repeated Angiography - Nützel, Regina; Brandt, Silvio; Rampp, Stefan; Leisz, Sandra; Simmermacher, Sebastian; Prell, Julian; Strauss, Christian; Scheller, Christian (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background The data on handling of spontaneous, nontraumatic subarachnoid hemorrhage (SAH) with negative initial digital subtraction angiography (DSA) are still inconclusive. The intention of this study was to evaluate the requirement of repeat DSA in patients with negative initial DSA and to compare the clinical outcomes of these cases.Methods In a retrospective study, we reviewed patients with SAH and negative initial DSA treated in our department from January 2006 until December 2017. The patients were divided according to an established radiographic classification into perimesencephalic (pm) and nonperimesencephalic (npm) SAH. An interventional neuroradiologist and a neurosurgeon reviewed all DSA scans.Results In all, 52 patients with negative initial DSA, comprising 36 (69.2%) patients with pm and 16 (30.8%) patients with npm bleeding pattern, were included. All patients underwent a second and 23 of these patients underwent a third DSA. In these 23 patients, subarachnoid blood distribution in the initial computed tomography (CT) scan was suspicious for the presence of aneurysm. In total, two aneurysms were detected during the second DSA (diagnostic yield: 3.85%). Both were in the pm group (diagnostic yield: 5.6%). The second repeat DSA did not show any causative vascular lesion. Complications after the DSA occurred in only 2 of 127 patients (1.6%). The rate of complications concerning vasospasm (pm 52.8%, npm 56.3%), hydrocephalus (pm 47.2%, npm 50%), and the need for temporary or permanent shunt (pm 44.4%, npm 50%) was similar in both groups and there was no statistically significant difference.Conclusion Repeat DSA after negative initial DSA in pm SAH had a diagnostic yield of 5.6%. However, a second repeat DSA cannot be recommended in case of SAH with initial negative DSA. The pm SAH should not be underrated concerning the occurrence of complications and cared with a high level of surveillance.
Keywords: subarachnoid hemorrhage; perimesencephalic hemorrhage; repeat angiography; aneurysm